Estimated changes in hospital admissions for alcohol intoxication after partial bans on off‐premises sales of alcoholic beverages in the canton of Vaud, Switzerland: an interrupted time–series analysis. (5th February 2020) - Wicki, Matthias; Bertholet, Nicolas; Gmel, Gerhard
Abstract: Aims: To estimate age‐specific changes in hospital admissions for alcohol intoxication following two consecutive restrictions on off‐premises alcohol sales introduced in the canton of Vaud, Switzerland. Design: Primary analyses used interrupted autoregressive integrated moving average (ARIMA) time–series analyses (repeated cross‐sectional), with Lausanne and Vaud as experimental sites and the rest of Switzerland as the control. Secondary analyses used, for example, a different control site (other French‐speaking cantons only) or a different statistical model. Setting: Switzerland between 2010 and 2016. Participants: In‐patients (i.e. patients assigned a bed overnight) hospitalized between 8 p.m. and 6 a.m. ( n  = 1 261 564), as documented in the Swiss Hospital Statistics. Interventions: Ban 1, only effective in the canton's capital, Lausanne, prohibited off‐premises sales of all alcoholic beverages after 8 p.m. on Fridays and Saturdays from September 2013 to June 2015. In July 2015, Ban 2 replaced this, covered the whole canton and affected off‐premises sales of beer and spirits (but not wine) after 9 p.m. (8 p.m. in Lausanne) every night of the week. Measurements: Proportions of monthly hospital admissions for alcohol intoxication (ICD‐10 diagnoses F10.0/F10.1, T51.0) per 1000 monthly overall admissions. Findings: Proportions of overall hospitalizations for alcohol intoxication declined after both bans in Lausanne [ωBan1  = −0.017, 95% confidence interval (CI) = −0.025, –0.008; ωBan2  = −0.021, 95% CI = −0.030, –0.013] but only after Ban 2 in the remainder of the canton of Vaud (ωBan2  = −0.008, 95% CI = −0.014, –0.002). Estimated changes in % were largest among 16–19‐year‐olds. However, as admission rates for alcohol intoxication were more frequent in adulthood than adolescence, the estimated change in number of cases was also relevant to public health among 20–69‐year‐olds. Secondary analyses supported the findings of the primary analyses. Conclusion: Even partial restrictions of off‐premises sales of alcohol in Switzerland (only 2 days per week or only for beer and spirits) appeared to reduce hospital admissions for alcohol intoxication across a wide age range (ages 16–69 years).